ANALISIS LERENG TERASERING DALAM UPAYA PENANGGULANGAN LONGSOR METODE FELLENIUS DENGAN PROGRAM GEOSTUDIO SLOPE - Dimas Haryadi; Mawardi Mawardi; Makmun R. Razali (Universitas Bengkulu, 2019)
The Musi Hydroelectric Power Plant area in Kepahiang Regency is a hilly area that has steep slopes that are prone to landslides. One of the landslides that occurred at October 2017 precisely occurred on a highway between Susup Village, Bengkulu Tengah Regency and Ujan Mas District, Kepahiang Regency. This study aims to analyze the slope stability of the terraces using the Fellenius Method. The results of testing the physical properties of the soil indicate that the soil on the slopes of the area of the Musi Hydroelectric Power Plant is clay. The slopes studied in the Musi hydropower area are all prone to landslides because safety factor, FK <1,5. Based on the results of the research on the slopes of the safest type 1 slope the value of the safety factor is the type of slope of the slope trap 3,19o,FK = 1,61 greater than the safety factor value of slope type 2 slope trap 19o, FK = 1,57 and safe slope type safety factor value slope of 19o, FK = 1.519 and the value of the safety factor of the original slope type of slope 30o, FK =0,88.